The role of particle size in the laboratory reflectance spectra of pyroxenes: The case of the 670-nm minor feature. (November 2015) - Mancarella, Francesca; Orofino, Vincenzo; Blanco, Armando; D'Elia, Marcella; Fonti, Sergio
Abstract: Reflectance spectroscopy is a very helpful tool for remote sensing investigations and has been widely used in terrestrial as well as planetary observations to study the surface composition. From this perspective, the visible (Vis) and near-infrared (NIR) regions of the spectrum, where several diagnostic absorption features of minerals are located, are well suited for the identification of such materials, in particular of rock-forming silicates. Among them, pyroxenes, which have been discovered on the surface of a number of different solar system bodies, play an important role. Up to now, both laboratory and remote sensing spectroscopic studies have been focused mainly on the two major bands at about 1 and 2 µm (the so-called Band I and Band II, respectively), while little attention has been paid to the minor bands falling in the visible range. One of the most important of them, present in many pyroxenes as well as in olivines, is the weak feature (reflectance minimum) near 670 nm, generally characterized by its variable wings (reflectance maxima) at about 570 nm and 720 nm. The intensity and the exact position of this feature depend on the type of pyroxene as well as on the grain size of the particles under consideration. In this work we present the Vis/NIR experimental reflectance spectra concerning enstatite and diopside, which are excellent representative of Low Calcium Pyroxenes (typically orthopyroxenes), and High Calcium Pyroxenes (typically clinopyroxenes) respectively. The results are very interesting and show a good correlation between the grain size of our samples and the relative intensities of the reflectance maxima occurring on both sides of the 670 nm feature. A similar study performed on Acfer 353, a pyroxene-rich eucritic meteorite of the Howardite–Eucrite–Diogenite family, of putative Vestan origin, shows that also in this case the variability in the Vis region of the spectra is linked to the grain size of the meteoritic particles. The connection between grain size and the behavior of the 670 nm feature can potentially be used to derive the average dimension of the regolith existing on the surface of planets and minor bodies. Both laboratory and observational study of the minor features, frequently ignored in the interpretation of the spectra acquired in remote sensing, can give complementary and useful information and thus can definitely contribute to a better knowledge of the mineralogy of planetary and asteroidal surfaces. Highlights: We measured Vis/NIR reflectance spectra of samples of enstatite and diopside. We found in pyroxenes a dependence of the minor 670 nm spectral band on grain sizes. We found a dependence of the spectral behavior on grain sizes in a HED meteorite. We suggest this could be used to infer the mean size of the Vestian regolith.